2022
DOI: 10.12928/jbns.v1i2.5232
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in isolation and identification of bacteria from Indonesia with various roles: Review Article

Abstract: Bacteria are agents that can be used widely and are genetically easy to manipulate and reproduce. Many studies related to the isolation and identification of bacterial isolates from Indonesia have been carried out for various purposes. This research is still ongoing and has never been informed about the abundance of data from previous studies. The purpose of this study is to provide an overview of research topic trends related to the isolation and identification of bacterial isolates from Indonesia. The method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…Based on Table 2, all bacterial isolates showed non-motile results, meaning that there was no bacterial movement during the 2-day incubation time as seen from the absence of propagation around the ose needle puncture. From some research results, it is stated that lactic acid bacteria are bacteria that do not have flagella so that movement is inhibited [29], [30]. In line with the research results [31] that lactic acid bacteria from Kepok Banana Tape showed non-motile bacteria or no bacterial dispersal.…”
Section: Results and Discussion Isolation Of Bacteria From Rice Washi...mentioning
confidence: 59%
“…Based on Table 2, all bacterial isolates showed non-motile results, meaning that there was no bacterial movement during the 2-day incubation time as seen from the absence of propagation around the ose needle puncture. From some research results, it is stated that lactic acid bacteria are bacteria that do not have flagella so that movement is inhibited [29], [30]. In line with the research results [31] that lactic acid bacteria from Kepok Banana Tape showed non-motile bacteria or no bacterial dispersal.…”
Section: Results and Discussion Isolation Of Bacteria From Rice Washi...mentioning
confidence: 59%